Amendment of Bank Conversion Agreement to Sharia Contract: Comparative Analysis of Positive Law and Fiqh of Muamalah - Humaira Humaira; Syahrizal Abbas; Hafas Furqani (Program Pascasarjana IAIN Langsa, 2026)
In positive law, changes to the terms of an agreement resulting from statutory provisions or legal mandates may be classified as a form of relative force majeure, depending on the extent to which such changes affect the parties' ability to perform their contractual obligations. A unilateral modification of an agreement pursuant to mandatory statutory provisions constitutes an exception to the principle of pacta sunt servanda. Such modification may be legally justified when it is required by binding legislation. This study examines the legal status of dormant accounts and their resolution under both Islamic law and positive law, as well as contract modifications made without customer consent from the perspective of fiqh muamalah. This research employs a normative legal method using statutory, conceptual, and comparative approaches. The data consist of primary legal materials, including statutory regulations and DSN-MUI fatwas, as well as secondary legal materials, such as books, journal articles, and other relevant literature. The data are analyzed through library research, legal interpretation, and legal construction, and the findings are presented using a descriptive qualitative approach. The results demonstrate that positive law and Islamic law can be harmonized in addressing contract modifications within Sharia agreements in the context of account conversion. Such modifications are implemented through contract amendments rather than contract termination, providing a legally valid solution under positive law while remaining consistent with Sharia principles, particularly the principles of mutual consent (riḍā), trust (amānah), and justice (ʿadl) in muamalah. A contract amendment constitutes a partial modification of the terms of an agreement carried out in accordance with the law without nullifying the contract as a whole. In the context of account conversion, this means that the original agreement remains legally valid, while its provisions are amended to ensure compliance with Sharia principles. This study recommends the issuance of specific regulations by the Financial Services Authority (OJK) or a DSN-MUI fatwa to address the existing legal vacuum.